Mechanisms underlying the beneficial effects of physical exercise on multiple sclerosis: focus on immune cells - Zong, Boyi; Yu, Fengzhi; Zhang, Xiaoyou; Zhao, Wenrui; Li, Shichang; Li, Lin (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is a prevalent neuroimmunological illness that leads to neurological disability in young adults. Although the etiology of MS is heterogeneous, it is well established that aberrant activity of adaptive and innate immune cells plays a crucial role in its pathogenesis. Several immune cell abnormalities have been described in MS and its animal models, including T lymphocytes, B lymphocytes, dendritic cells, neutrophils, microglia/macrophages, and astrocytes, among others. Physical exercise offers a valuable alternative or adjunctive disease-modifying therapy for MS. A growing body of evidence indicates that exercise may reduce the autoimmune responses triggered by immune cells in MS. This is partially accomplished by restricting the infiltration of peripheral immune cells into the central nervous system (CNS) parenchyma, curbing hyperactivation of immune cells, and facilitating a transition in the balance of immune cells from a pro-inflammatory to an anti-inflammatory state. This review provides a succinct overview of the correlation between physical exercise, immune cells, and MS pathology, and highlights the potential benefits of exercise as a strategy for the prevention and treatment of MS.